2001
DOI: 10.1021/es001740a
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorocyclohexane (HCH) Isomers and Chiral Signatures of α-HCH in the Arctic Marine Food Web of the Northwater Polynya

Abstract: Concentrations of hexachlorocyclohexane (HCH) isomers (alpha, beta, and gamma) and enantiomer fractions (EFs) of alpha-HCH were determined in the Northwater Polynya Arctic marine food web. Relative food web structure was established using trophic level models based on organic delta 15N values. Concentrations of HCH in the samples collected, including water, sediment, benthic invertebrates (four species), pelagic zooplankton (six species), Arctic cod, seabirds (seven species), and ringed seal, were in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
90
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 40 publications
(56 reference statements)
12
90
1
1
Order By: Relevance
“…Their decreasing trend were very significant (p = 0.001) during this time span; these Authors reported that α-HCH concentrations declined faster than those of δ-HCH, in agreement with observations for Arctic air and water (Li et al, 1998;Jantunen and Bidleman, 1995). The HCH isomer abundance were α-HCH > β-HCH > δ-HCH in Polar cod (Sinkkonen et al, 2000;Moisey et al, 2001) and δ-HCH > α-HCH > β-HCH in the Antarctic T. bernacchi (Corsolini et al, 2006). These patterns could be interpreted as an indication that the use of technical HCH (containing 60-70% of α-HCH) has decreased faster than that of pure lindane (Li et al, 1998).…”
Section: Hchs In Arctic Biotasupporting
confidence: 82%
See 2 more Smart Citations
“…Their decreasing trend were very significant (p = 0.001) during this time span; these Authors reported that α-HCH concentrations declined faster than those of δ-HCH, in agreement with observations for Arctic air and water (Li et al, 1998;Jantunen and Bidleman, 1995). The HCH isomer abundance were α-HCH > β-HCH > δ-HCH in Polar cod (Sinkkonen et al, 2000;Moisey et al, 2001) and δ-HCH > α-HCH > β-HCH in the Antarctic T. bernacchi (Corsolini et al, 2006). These patterns could be interpreted as an indication that the use of technical HCH (containing 60-70% of α-HCH) has decreased faster than that of pure lindane (Li et al, 1998).…”
Section: Hchs In Arctic Biotasupporting
confidence: 82%
“…Fish species collected in the Arctic region and analyzed for HCHs were mostly the Arctic cod (Arctogadus glacialis), the Polar cod (Boreogadus saida), the Greenland halibut (Reinhardtius hippoglossoides), and others. ΣHCH concentrations in Polar cod muscle from the Canadian Arctic were 90.2±13.7 ng/g lipid wt (Moisey et al, 2001), 40±3.2 ng/g lipid wt (Hoekstra et al, 2003), and 10 ng/g lipid wt (Kelly et al , 2008); concentrations in the Greenland halibut muscle were as 81 ng/g lipid wt in (Fisk et al, 2002), and 53 ng/g lipid wt in Greenland shark (Somniosus microcephalus) liver (Fisk et al, 2002). Levels in Polar cod were of the same order of magnitude, but a decreasing trend can be observed during 2000s.…”
Section: Hchs In Arctic Biotamentioning
confidence: 95%
See 1 more Smart Citation
“…Contaminant's half-lives were assumed long as invertebrates and fish have restricted or negligible biotransformation of PCBs (e.g. Moisey et al, 2001). (D) Diet composition: Copepods- Scott et al (1999), Euphausiids-Båmstedt and Karlson (1998), Amphipods-Scott et al (1999), Polar cod- Lønne and Gulliksen (1989).…”
Section: Total Particulate Matter Concentrationmentioning
confidence: 99%
“…Moisey et al, 2001), assuming that POP partition only into lipids and not other organic phases is debated (e.g. Swackhamer and Skoglund, 1993;Skoglund and Swackhamer, 1999).…”
Section: Bioaccumulation Factors and Equilibriummentioning
confidence: 99%